PROTOTYPE ROBOT TEMPAT SAMPAH MENGGUNAKAN ANDROID BERBASIS MIKROKONTROLER ATMEGA 328 PADA PERGURUAN TINGGI RAHARJA - Ageng Setiani Rafika; Dian Koswara; Budi Nugroho (Universitas Insan Pembangunan Indonesia, 2016)
ABSTRACTIn the present era, we often see people do the taking the trash using human power. The trash can is the place tohold unused junk again temporarily. And garbage is leftover materials from humans, animals, or plants that areunused anymore and released to nature in the form of a solid, liquid, or gas. Often we see the way people throwtrash in the trash can be done manually, using only the hands. For these problems, then the author developed atool called the trash robot using android as a governing tool. And using the Atmega328 as controlling andpenginputan programs. This tool also uses a system of basic line follower contained sensors to detect line ontracks and servo motor as the pengerak wheels, claws, and a dumpster.Keyword: Android, Atmega328, Photodioda Sensor, Servo Motor